2022
DOI: 10.1039/d1cp03363h
|View full text |Cite
|
Sign up to set email alerts
|

Nontrivial topological defects of micro-rods immersed in nematics and their phototuning

Abstract: Combinations of different geometry and the surface anchoring conditions give rise to the diversity of topological structures in nematic colloid systems. Tuning these parameters in a single system offers possibilities...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
(55 reference statements)
2
1
0
Order By: Relevance
“…Aya homeotropic surface anchoring. 29 The defect structure of our rods appears to be nontrivial and similar to those reported by Aya et al 29 which implies the surface anchoring of the rods in NLC is weak. First we study the DC electrophoresis of the rods in cells with inplane electrodes.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Aya homeotropic surface anchoring. 29 The defect structure of our rods appears to be nontrivial and similar to those reported by Aya et al 29 which implies the surface anchoring of the rods in NLC is weak. First we study the DC electrophoresis of the rods in cells with inplane electrodes.…”
Section: Resultssupporting
confidence: 84%
“…Aya et al have studied even bigger microrods ( L ≃ 60 μm and D ≃ 10 μm) dispersed in azodendrimer doped NLC which provides weak homeotropic surface anchoring. 29 The defect structure of our rods appears to be nontrivial and similar to those reported by Aya et al 29 which implies the surface anchoring of the rods in NLC is weak.…”
Section: Resultssupporting
confidence: 84%
“…These are nontrivial defects as they are pinned on the particle and not visible as reported in the case of similar rod-like particles. 30,[37][38][39] For much smaller rods (L E 50 nm and D E 10 nm), B. Senyuk et al have reported different virtual defects. 40 For larger silica micro-rods (L = 8 mm and D = 1.5 mm), actual defects are seen much more clearly near the rods.…”
Section: A Topological Defectsmentioning
confidence: 99%